CO151 Impact of the rational antibiotic use system on hospital performance at Cartagena Colombia from 2018 to 2021 (2023)
To describe the experience carried out with the implementation and the Impact of the Rational Antibiotic Use System on Hospital Performance, at Cartagena, Colombia from 2018 to 2021, and the progressive decrease in the consumption of control antibiotics monitored by the National Institute of Health (INS). Compared to national and departmental averages.